Insertion site of FLAG on foot-and-mouth disease virus VP1 G-H loop affects immunogenicity of FLAG - Yuan-yuan ZHU; Xing-qi ZOU; Hui-fang BAO; Pu SUN; Xue-qing MA; Zai-xin LIU; Hong-jie FAN; Qi-zu ZHAO (Journal of Integrative Agriculture, 2018)
The G-H loop of the foot-and-mouth disease virus (FMDV) virion contains certain dominant immunogenic epitopes, as well as an arginine-glycine-aspartic acid (RGD) motif that is recognized by cell surface integrin receptors. Previous experiments indicate that it is critical to maintain virus structural integrity when inserting an exogenous epitope into the surface of an FMDV structural protein. However, it remains to be determined how factors such as different insertion positions affect interactions among the virus, cells and host immune system. In this study, one infectious cDNA clone of the swine FMDV Cathay topotype strain O/CHA/90 was constructed. Then, a FLAG marker (DYKDDDDK) was inserted upstream (–4) or downstream (+10) of the RGD motif to generate tagged viruses vFLAG-O/CHA/90 or vO/CHA/90-FLAG, investigating the possibility of expressing foreign antigen and effect on its immunogenicity. Compared to the parental virus, both tagged viruses exhibited similar plaque phenotypes, suckling mouse pathogenicity and antigenicity. Additionally, the FLAG tag insertion position did not change the use of integrin-mediated cell entry by the tagged viruses. Interestingly, both tagged vaccines protected pigs against challenge with the parental virus O/CHA/90 and induced immune responses against FMDV in BALB/c mice and pigs, but only vaccination with vFLAG-O/CHA/90 generated anti-FLAG antibodies. Our findings demonstrated that two sites (RGD–4 and RGD+10) tolerated the insertion of an exogenous gene in the swine FMDV O/CHA/90 strain. However, only RGD–4 was a novel and appropriate inserting site which could tolerate exogenous FLAG. The resultant tagged virus is a promising candidate for FMD vaccine which can be differentiating infected from vaccinated animals (DIVA).